O kwalifikowanych typach zabójstwa we francuskim prawie karnym - Brzezińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The aim of the article is to present the types of aggravated homicide in French criminal law. The author focuses on the basic categories of premises affecting the possibilityof tightening criminal liability for homicide in the French Criminal Code. The factors constituting the basis for classification indicated in the article include the victim’s status on account of age, background, function preformed, the perpetrator’s motivation discrimination on ethnic, racial and religious grounds, the number of perpetrators participation in an organised criminal group and a particular form of intent premeditation. In addition, the author analyses the issue of sentencing modification in the given category of crimes.
Keywords: zabójstwo; przestęstwo zaostrzone; morderstwo z premedytacją